Reconstructing the Legal Architecture of Crypto Asset Issuance Regulation in Indonesia - Aloysius Bernanda Gunawan; Adi Nur Rohman; M.S. Tumanggor (Transpublika Publisher, 2026)
Indonesia's crypto asset ecosystem has grown substantially, ranking sixth globally in adoption, yet its regulatory architecture for crypto asset issuance remains fragmented and inadequately defined. This study examines the evolutionary trajectory of Indonesia's issuance-related regulatory framework, tracing the shift from the commodity-based positive-list regime under Surat Keputusan (SK) Bappebti Number 13 of 2022, through the transition to financial sector governance under Peraturan OJK (POJK) Number 27 of 2024, and the subsequent amendments introduced by POJK Number 23 of 2025. Employing a normative juridical method with comparative law and statutory approaches, this study benchmarks Indonesia's framework against the European Union's Markets in Crypto-Assets (MiCA) Regulation (EU) 2023/1114 currently the most comprehensive issuance-specific crypto asset law globally. The analysis reveals six critical regulatory gaps in Indonesia's issuance regime, including the absence of a formal white paper obligation, the lack of pre-issuance issuer authorization, no technical due diligence mandates, and an inadequate disclosure liability framework. In response, this article proposes a Three-Gate Regulatory Architecture Model comprising Gate I (Registration and White Paper Validation), Gate II (Technical Due Diligence), and Gate III (OJK Approval and License Issuance), complemented by transitional provisions for existing assets. This model represents a legally grounded and proportionate reconstruction of Indonesia's crypto asset issuance regulation, aligned with international best practices while respecting Indonesia's regulatory sovereignty.